Quranic Argument of Perennial Philosophy by “The Traditional School of Thought”: An Analytical Study - Mian Swaiz Nadeem; Dr. Hafiz Tahir Islam (Journal of Religion and Society, 2025)
Modernity in the Muslim world is considered to be the most influential cause for the new interpretations of Qur’anic Verses. It was the 19th and 20th Centuries that the Scientific and Political Interpretations came into existence. In the late 19th and early 20th century, a new school of thought, established in France, England and many other parts of Europe, highly influential not only the Europe & America, but also influential in the Malaysia, Egypt, Pakistan and Iran. It was named “The Traditional of Perennial School of thought”. They developed the perennial philosophy combining all the metaphysical truths and unity of Religions. They provided enormous arguments about the inner unity of religions and the perennial nature of man .Does all the religion came from the same source? Hinduism, Confucius, Judaism, Christianity and Islam discussed the same truth in different forms? This school of thought mentioned many Qur’anic verses as an arguments for their perennial claims, however they are deeply concerned with Islam and Quran. They claim that the above mentioned religions, are still functioning in a way that they make a way or road to God. This article inquires Qur’anic arguments of perennial philosophers, mentions some of the interpretations of the early Qur’anic interpreters. Keywords: Quran, Perennial philosophy, Book of people, Unity of Religion.